Classification of two-dimensional Jordan algebras - Ahmad, Houida; Bekbaev, Ural; Rakhimov, Isamiddin (American Institute of Physics, 2017)
A classification, up to isomorphism, of two-dimensional (not necessarily commutative) Jordan algebras over any algebraically closed field is presented in terms of their matrices of structure constants.